Expert project management system (E-PMS) worker module in android / Nurliyana Mohammad Sanusi - Mohammad Sanusi, Nurliyana (2013)
Organizing the task or action is really important in life. Today, there are so many system technologies develop to facilitate people in organizing their activities such as project management system. The existing system had all the function for organizing the task but not for calculation function which is to compare the estimation cost and real cost. Worker sometimes are late informed the finished task to their project manager. The main research is to create cost calculation function in android platform. Other than that, the objective also is to create notification status of completed task to project manager and develop notification project assign to worker by email. For this project, rapid application development (RAD) method has been chosen for developing the system. This type of methodology allows fast implementation of the system in real environment. There are six phases in rapid application development which are analysis and quick design, develop, demonstrate, refine, testing and lastly deployment. At the end of development, the result of the proposed system should be working efficiently.